2012
DOI: 10.1002/ird.1660
|View full text |Cite
|
Sign up to set email alerts
|

How Does Unequal Access to Groundwater Contribute to Marginalization of Small Farmers? The Case of Public Lands in Algeria

Abstract: The use of groundwater in irrigated agriculture is often regarded as an effective way of increasing farm productivity. However, the effects of differential access to groundwater by farmers have rarely been studied at the microeconomic scale, particularly the possibly negative effects of marginalization of small farmers. During the hydraulic crisis that has affected Algerian irrigation schemes since the 1980s, groundwater has become a major source of irrigation for farmers. A process of farm differentiation occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
0
9
0
5
Order By: Relevance
“…It is mainly small-scale farmers (<2 ha) who are left behind . A recent study in the Cheliff irrigation scheme (Algeria) showed that only 38 % of farmers had access to groundwater, while the remaining farmers were "trapped in a process of impoverishment" (Amichi et al 2012). The second source of inequality is the pump equipment as we showed for the Saiss.…”
Section: Groundwater As the Enabler Of A Socio-economic Transitionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is mainly small-scale farmers (<2 ha) who are left behind . A recent study in the Cheliff irrigation scheme (Algeria) showed that only 38 % of farmers had access to groundwater, while the remaining farmers were "trapped in a process of impoverishment" (Amichi et al 2012). The second source of inequality is the pump equipment as we showed for the Saiss.…”
Section: Groundwater As the Enabler Of A Socio-economic Transitionmentioning
confidence: 69%
“…More than 10 % of the world's food production depends on aquifers that are overexploited and threatened (Postel 1999). In addition, inequalities in groundwater access, often building on the individual's position in society, were shown to contribute to marginalization of certain categories of farmers and to favour social differentiation (Prakash 2005;Amichi et al 2012). According to this view, the growing anarchy in the exploitation of groundwater for irrigation is due to 'inherent' features of the groundwater economy, i.e.…”
Section: Introduction: Private Groundwater Use In a Context Of State-mentioning
confidence: 99%
“…Inversely, based on several case studies in South Asia, Shah () argues that groundwater markets have made the benefits of groundwater access available to an estimated 50–70 million smallholder farmers, who would have been unable to invest in their own tubewell. At the same time, it was shown that groundwater has become an important factor in the social and economic differentiation of farmers (Prakash, ; Amichi et al , , this issue). By building on existing inequalities in landholding, bigger farmers were shown to obtain better access to groundwater, thereby marginalizing certain categories of farmers.…”
Section: Groundwater: From Nuisance To (Contested) Fortunementioning
confidence: 99%
“…The access to groundwater of farmers on public lands in Algeria was shown to be made possible through informal arrangements (Figure ) and to be linked to land markets (Imache et al , ; Ammar Boudjellal et al , ; Amichi et al , , this issue). Public lands are characterized by complex and rapidly evolving land tenure systems, with the presence of many informal lessees.…”
Section: Groundwater Governance: Taking Existing Experiences Into Accmentioning
confidence: 99%
“…Their role is not even acknowledged in water management and water policies. This can be explained by the fact that these actors operate in a context in which access by farmers to production factors (land, water, inputs) and markets is highly informal (Amichi et al 2012(Amichi et al , 2016Fofack et al 2015;Daoudi and Colin 2016;Daoudi 2016). There is even a tendency in the literature to link Binformal^with Bunstructured^and Bdisorganized^ (Guha Khasnobis et al 2006).…”
Section: Introductionmentioning
confidence: 96%